Development of modified nucleosides for targeting the DNA repair enzyme SNM1A - Berney, Mark (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Certain cancers exhibit upregulation of DNA interstrand crosslink repair pathways, which contributes to resistance to crosslinking chemotherapy drugs and poor prognoses. Inhibition of enzymes implicated in interstrand crosslink repair is therefore a promising strategy for improving the efficacy of cancer treatment. One such target enzyme is SNM1A, a zinc dependent 5 -3 exonuclease. Human cells deficient in SNM1A, as well as whole mice deficient in SNM1A, show increased sensitivity to crosslinking chemotherapy agents. Previous studies have demonstrated the feasibility of inhibiting SNM1A using modified nucleosides appended with zinc-binding groups. There remains a need however to develop improved inhibitors for this enzyme. Furthermore, due to the complexity of interstrand crosslink repair, and the additional functions of SNM1A in cell cycle checkpoint pathways, the biological role of this enzyme has yet to be fully elucidated. The development of chemical probes to study SNM1A in a cellular environment would facilitate further research in this area, allowing the full potential of this enzyme as a drug target to be explored. The work presented herein aimed to further the development of modified nucleosides for binding to SNM1A. Zinc-binding groups previously untrialled against SNM1A, including sulfonamide, 2-thiophene carboxamide, oxime, and hydroxylamine moieties, were incorporated at the 3 -position of nucleoside derivatives. Biochemical testing of these compounds showed that sulfonamide and hydroxylamine zinc-binding groups are effective. Modified nucleosides were also prepared bearing a hydroxamic acid and a hydrazide at the 3 -position, zinc-binding groups previously trialled at the 5 -position of SNM1A inhibitors. The synthesis of a family of squaramide- and thiosquaramide-bearing nucleoside derivatives and their evaluation as SNM1A inhibitors is also described in this work. Initial screening identified N hydroxysquaramide, squaric acid, and thiosquaramide moieties as promising zinc-binding groups for targeting SNM1A. Nucleoside derivatives bearing squaramides at the 3 -position were found to be more effective inhibitors than those bearing squaramides at the 5 -position. The reverse trend was observed in the case of thiosquaramides. Quantitative IC50 determination showed that a thymidine derivative bearing a 5 thiosquaramide was the most potent inhibitor, followed by a thymidine derivative bearing a 3 -squaric acid. UV-vis titrations were performed to study the binding interactions of the (thio)squaramides with zinc ions, allowing the order of potency of the SNM1A inhibitors to be rationalised. The membrane permeability of the active inhibitors was investigated, with several compounds showing promise for future in vivo applications. The development of more effective SNM1A inhibitors through exploiting interactions with the phosphate-binding pocket adjacent to the enzyme s active site, in addition to targeting the catalytic zinc ions, was also investigated in this work. A series of nucleoside derivatives bearing phosphate moieties at the 5 position, as well as zinc-binding groups at the 3 position, were prepared and tested. This showed that incorporation of a 5 phosphate dramatically increased the potency of the inhibitors. Overall, the results presented in this work represent significant progress in the development of nucleoside-based SNM1A inhibitors. Insights generated will inform the design of next generation SNM1A inhibitors, and elaboration of inhibitor structures will also enable the development of chemical probes to study SNM1A in vivo.
APPROVED
Keywords: DNA repair; Nucleotide; Nuclease inhibitor; Squaramide; Zinc-binding group